Alkenone unsaturation during virus infection of Emiliania huxleyi. (September 2017) - Fulton, James M.; Kendrick, B. Jacob; DiTullio, Giacomo R.; Van Mooy, Benjamin A.S.
Highlights: Alkenone content increases during virus infection of E. huxleyi . Infected E. huxleyi cultures were relatively enriched in C37:2 and C38:2 alkenones. Autoxidation in infected cultures might decrease C37:3 and C38:3 alkenone content. Biomass from infected E. huxleyi could cause high alkenone-based temperatures. Abstract: Alkenones are found in diverse prymnesiophytes including Emiliania huxleyi, which ranges throughout the world ocean. The number of double bonds in alkenones corresponds with growth temperature, and calibrations between sea surface temperature and alkenone unsaturation have been used to establish alkenone unsaturation as a temperature proxy in ancient sediments. Here we report virus infection causes a relative increase in the proportion of diunsaturated alkenones in E. huxleyi strain CCMP 374. As virus infection routinely terminates E. huxleyi blooms in the ocean, it is possible that this contributes to the variance in alkenone-based temperature estimates for core-top sediments.